Analisis Kinerja Keuangan Terhadap Return Saham Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012–2023" - Tikasari, Nopi; Arreski, Dwi Fitra (Innovative: Journal Of Social Science Research, 2024)
This study aims to examine the effect of financial performance on stock returns of mining companies listed on the Indonesia Stock Exchange during the period 2012–2023. The research sample was selected using purposive sampling techniques based on specific criteria, resulting in 144 samples from 12 mining companies. Data analysis was conducted using panel regression with the help of Microsoft Excel and Eviews 12 software. The independent variables used in this study include Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Earnings Per Share, while the dependent variable is Stock Return. The analysis results show that: (1) Current Ratio does not have a significant effect on Stock Return; (2) Debt to Equity Ratio does not have a significant effect on Stock Return; (3) Earnings Per Share does not have a significant effect on Stock Return; and (4) Net Profit Margin has a positive and significant effect on Stock Return. Further research is recommended to include additional variables and extend the research period to obtain more comprehensive results.